Role of minimally invasive surgery in cardiac valve disease - Potwar, Sushrut; Shende, Shweta; Nagle, Kanak; Pohekar, Pankaj; Nathani, Rahul; Nair, Hari (International Journal of Medical Research and Review, 2016)
Introduction: Over the past decade minimally invasive cardiac surgery has gained significant popularity, more cases of valve, bypass and congenital surgery are being done by smaller incisions as experience increases. Materials & Methods: Between January 2013 and December 2015 a total of 50 cases were performed using ministernotomy or right thoracotomy. The patients were between 17-58 years of age and included 29 males, 21 females. Results: In Minimally invasive surgery average pump time was 20-60 minutes, cross clamp time 30-50 minutes, ventilation <8 hours, ICU stay < 1day, 2 or less units of blood required in majority of patients. Conclusion: Minimally invasive cardiac surgery results in smaller incisions, shorter ventilator time, ICU and hospital stay, faster recovery, less pain, lower incidence of infection and bleeding and better cosmesis.